Unlocking new frontiers in epilepsy through AI: From seizure prediction to personalized medicine - Majd A. AbuAlrob (22392505) (2025)
Artificial intelligence (AI) is revolutionizing epilepsy care by advancing seizure detection, enhancing diagnostic precision, and enabling personalized treatment. Machine learning and deep learning technologies improve seizure monitoring, automate EEG analysis, and facilitate tailored therapeutic strategies, addressing the complexities of epilepsy management. However, challenges remain, including issues of model accuracy, interpretability, and applicability across diverse patient populations. Ethical considerations, such as safeguarding patient privacy, ensuring data security, and mitigating algorithmic bias, underscore the importance of responsible AI integration. Collaborative efforts among neurologists, data scientists, and regulatory authorities are critical to refining models, establishing ethical guidelines, and ensuring safe clinical adoption. This review examines AI’s transformative potential, its current limitations, and the multidisciplinary initiatives driving its effective implementation in epilepsy care. Other Information Published in: Epilepsy & Behavior License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.yebeh.2025.110327